(untitled) (mathematica didactica, 2021)
This article gives an overview of instruments und designs applied in studies published in English and German (N = 30) since 1998 measuring mathematics anxiety among pre-service teachers. Additionally, findings from intervention studies (N = 14) will be presented that aimed at the reduction of math anxiety. The review shows that math anxiety among pre-service teachers has been assessed pre-dominantly by inventories presenting mathematics-related situations. In addition to the prevalence of math anxiety, findings refer to the correlation of math anxiety with math proficiency/qualification in math, competence beliefs, prior experience in school, math-related attitudes/beliefs, and anxiety to teach mathematics. Further results are given for differences of gender, subject choice, and years of study in the teacher education program. Courses in mathematics didactics were the most common form of intervention that proved effective in reducing math anxiety.